Sensitive Interventions in Overcoming Chronic Energy Deficiency of Pregnant Women in A Northern Coastal City of Central Java - Yuliati, Erni; Sriatmi, Ayun; Suryoputro, Antono (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
Pregnant women with Chronic Energy Deficiency (CED) can cause health problems for both mother and baby. Among them are babies with low birth weight (LBW), who are at risk of stunting. The Pekalongan City Government issued Mayor Regulation Number 11 of 2023 concerning the Acceleration of Integrated Stunting Reduction, where the group of CED pregnant women is one of the targets of Stunting-prone Families who need specific and sensitive interventions. This study aimed to analyze implementation of the policy, especially sensitive interventions of CED pregnant women in Pekalongan City. This study used a descriptive qualitative method. The research was conducted from August to September 2024. The object of the study was the implementation of sensitive interventions of CED pregnant women which was analyzed with Van Metter-Van Horn policy implementation model. The research was conducted through in-depth interviews, observation and documentation. The determination of informants used a non-probability technique with a purposive method, and 11 informants were obtained. The stages in data analysis were data collection, reduction, presentation, data verification and conclusion drawn. The results of the study found that sensitive interventions in form of access to clean drinking water and sanitation, housing improvement programs, social assistance recipient programs and training facilitation for families of CED pregnant women are still not optimal. Pregnant women in CED had not been considered as a priority in obtaining the benefits of assistance programs. It needed to be improved again in policy socialization, quality and quantity of resources, coordination and communication, and improvement of the environmental situation.